Development and feasibility testing of an interactive avatar education application for education of patients with heart failure. (2nd June 2020) - Du, Huiyun; Wonggom, Parichat; Burdeniuk, Christine; Wight, Justin; Nolan, Paul; Barry, Tracey; Nesbitt, Katie; Clark, Robyn A
Abstract : Background/aims: Heart failure self-care is important for achieving optimal patient outcomes. Interactive information technology has been shown to enhance self-care knowledge and behaviours. This study aimed to codevelop and evaluate with consumers an avatar app for teaching heart failure self-care. Methods: Consumer participation and pre-post test methods. Findings: A total of six heart failure patients, two patients' family members and 15 heart failure clinicians and app developers participated in the development of the app. Overall, 13 people completed the app's feasibility testing and demonstrated a significant improvement in heart failure knowledge ( P =0.020), self-care maintenance ( P =0.027) and self-care confidence ( P =0.002). Self-care management did not improve significantly ( P =0.113) and satisfaction with learning using the app was very high (90%). Conclusions: The codevelopment approach used in this project resulted in a high level of user satisfaction. Consumers felt the app was a very feasible mechanism of heart failure education delivery.